The power of cross-cultural communication: reception and impact of Chinese variety shows on YouTube - Zhang, Yiyin (Frontiers in Communication, 2025)
This work investigates the international communication effects of Chinese variety shows on the YouTube platform from the perspective of cross-cultural communication using data analysis, text analysis, and communication strategy research. It is found that program genre, linguistic adaptability, presentation of universal values, and program guest selection influence cross-cultural communication to some extent. Accordingly, the effective ways to enhance the cross-cultural communication effect of Chinese variety shows include strengthening the innovation of program genres, improving the language adaptability and universal values of programs, and optimizing the selection of program guests. In cross-cultural communication, Chinese variety shows should also transform “cultural discount” into “cultural premium,” improve the operation ability of international platforms, and promote accurate global communication through localization.